Perkembangan Inovasi Teknologi pada Akuntansi Lingkungan: Analisis Bibliometrik Tren Publikasi Ilmiah dan Kolaborasi Penelitian Internasional Tahun 2015–2025 - Aprizal Ahmadi; Fania Juni Arsih; Deli Maharani; Marwa Fitri Ramdani; Intan Natial Fatrissia; Faidil Ramadan (Indo Publishing, 2026)
The rapid development of digital technology has significantly transformed various sectors, including environmental accounting, which plays a crucial role in supporting sustainable business practices. The integration of technologies such as accounting information systems, digital transformation, artificial intelligence, and data-driven technologies has increasingly been adopted to improve the management and reporting of environmental information. This study aims to map the development of scientific publications, identify dominant research themes, and analyze research trends related to technological innovation in environmental accounting during the 2015–2025 period. A descriptive quantitative approach employing bibliometric analysis was used. Data were collected from the Scopus database through a systematic filtering process based on publication period, subject area, document type, keyword relevance, and publication language. From an initial dataset of 61,079 documents, 5,456 articles met the analysis criteria. Bibliographic data were analyzed using VOSviewer through network, overlay, and density visualizations. The findings indicate a significant increase in studies addressing technological innovation in environmental accounting. Network visualization reveals that digital transformation serves as the central research theme, strongly connected with environmental accounting, accounting information systems, sustainability, innovation, and information management. Overlay visualization highlights a shift from traditional topics toward emerging themes such as digital technologies and artificial intelligence. These results demonstrate the growing role of digital technologies in enhancing transparency, accountability, environmental data management efficiency, and sustainability-oriented decision-making.